2020
DOI: 10.1101/2020.02.17.953075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated cell cycles enable organ regeneration under developmental time constraints in theDrosophilahindgut

Abstract: Individual organ development must be temporally coordinated with development of the rest of the organism. As a result, cell division in a developing organ occurs on a relatively fixed time scale.Despite this, many developing organs can regenerate cells lost to injury. How organs regenerate within the time constraints of organism development remains unclear. Here, we show the developing Drosophila hindgut regenerates by accelerating the mitotic cell cycle. This process requires JAK/STAT signaling and is achieve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Similarly, recently published experiments have observed that damage of the Drosophila hindgut during L2 or early L3 produces Dilp8, delaying the onset of pupariation, whereas damage to the hindgut of wandering L3 larvae no longer produces Dilp8 or developmental delay. However, regeneration is still completed in this attenuated period through accelerated mitotic cycling, which allows the tissue to meet the regeneration target within the mitotic regeneration window (Cohen et al, 2021). In this example, while ecdysone signaling regulates the end of mitotic regeneration, the role of ecdysone signaling in producing the accelerated mitoses has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recently published experiments have observed that damage of the Drosophila hindgut during L2 or early L3 produces Dilp8, delaying the onset of pupariation, whereas damage to the hindgut of wandering L3 larvae no longer produces Dilp8 or developmental delay. However, regeneration is still completed in this attenuated period through accelerated mitotic cycling, which allows the tissue to meet the regeneration target within the mitotic regeneration window (Cohen et al, 2021). In this example, while ecdysone signaling regulates the end of mitotic regeneration, the role of ecdysone signaling in producing the accelerated mitoses has not been investigated.…”
Section: Discussionmentioning
confidence: 99%